Damage assessment proposal for two bridges located on Highway No. 14 in the State of Sonora México by using stiffness invariant as global comparison parameter - Ramos-Torres, Gilberto; Navarro-Gómez, Humberto; Pérez-Isidro, Eber; Gautherau-López, Jorge; Palma Quiroz, Israel (Revista ALCONPAT, 2021)
The elastic rigidity invariant method is used to obtain the mechanical response of the superstructure of simply supported bridges; it is based on the bridge’s response to the impact of known masses applied on mid span to obtain the maximum displacement that defines the point stiffness. This value is compared with the values of the theoretical curve formed with the stiffness invariants, constructed from the design characteristics of the bridge. The method was implemented in two bridges located on federal highway No. 14 of the State of Sonora Mex., with results according to the damage manifested. The evaluation is the result of a global parameter, obtained in environmental conditions in the absence of wind and at a constant temperature, suitable for the diagnosis of the present structural state, having limitations on bridges with screw cross sections.